The Meaning of Love in the Lyrics of Tiara Andini’s Song Kupu-Kupu: A Semiotic Analysis of Ferdinand de Saussure - Indarsih, Mike; Horidatul Bakiyah; Fajar Diah Astuti; Faikoh Umairoh; Nabila Tri Rahmawati (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study aims to analyze the meaning of love in the lyrics of Tiara Andini’s song Kupu-Kupu using Ferdinand de Saussure’s semiotic theory. The research method used is qualitative descriptive with a semiotic approach. Data were obtained from the lyrics of the song Kupu-Kupu by Tiara Andini, which was released in 2023. The analysis is focused on identifying the relationship between the signifier and the signified in the song lyrics to uncover the denotative and connotative meanings contained within the expressions of love. The results of the study show that the lyrics of the song represent love as a complex emotional journey filled with hope, uncertainty, and transformation. The butterfly (kupu-kupu) is used as a symbol of beauty and change, which reflects the emotional development of someone who is experiencing love. Through its poetic language, the song conveys emotional nuances that align with Saussure’s semiotic elements. This study concludes that Kupu-Kupu portrays love not only as a feeling but also as a process of personal growth and self-discovery.